The relationship between beliefs towards mental illness and psychological help-seeking attitudes of medical vocational high school students (Annals of Medical Research, 2021)
Aim: The aim of this study was to evaluate the relationship between beliefs towards mental illness and psychological help-seeking attitudes of medical vocational high school students. Material and Methods: The sample of this analytical study consisted of 364 students studying at a medical vocational high school from February 1, 2019 to March 31, 2019. Data were collected using Student Information Form, Belief towards Mental Illness Scale and Attitudes toward Seeking Psychological Help Scale-Shortened. Descriptive data were analyzed using Mann–Whitney U-test and Spearman’s rank correlation coefficient test since data were not normally distributed.Results: The mean total Belief towards Mental Illness Scale score of the students was 50.08±17.32. The mean scores of subscales were 22.31±7.66 for dangerousness, 2.12±2.75 for embarrassment, and 50.08±17.32 for desperateness/poor social and interpersonal skills. The mean scores of positive and negative psychological help-seeking attitudes of the students were 46.79±10.51 and 21.33±5.92, respectively. Positive psychological help-seeking attitude was found to have a weak and negative correlation with dangerousness (r=0.131) and desperateness (r=0.107) subscales whereas a weak and positive correlation was observed with the embarrassment (r=0.202) subscale (p0.05). Negative psychological help-seeking attitudewas found to have a moderate and negative correlation with the total Belief towards Mental Illness Scale (r=0.328) scores, embarrassment (r=0.364) and desperateness (r=0.328) subscales whereas a weak and negative correlation was observed with the dangerousness (r=0.159) subscale (p0.05). Conclusion: This study has shown that beliefs of the medical vocational high school students towards mental illness are at a moderate level whereas their psychological help-seeking attitudes are high. Furthermore, students’ beliefs towards mental illness have been found to affect their psychological help-seeking attitudes. In line with these results, we believe that there is a need for studies that will improve students’ beliefs towards mental illness in a positive way.
Keywords: Adolescence; mental illness; psychological help-seeking; belief; attitude